If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4b + -10) = 2(9b + 3) Reorder the terms: 9(-10 + 4b) = 2(9b + 3) (-10 * 9 + 4b * 9) = 2(9b + 3) (-90 + 36b) = 2(9b + 3) Reorder the terms: -90 + 36b = 2(3 + 9b) -90 + 36b = (3 * 2 + 9b * 2) -90 + 36b = (6 + 18b) Solving -90 + 36b = 6 + 18b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-18b' to each side of the equation. -90 + 36b + -18b = 6 + 18b + -18b Combine like terms: 36b + -18b = 18b -90 + 18b = 6 + 18b + -18b Combine like terms: 18b + -18b = 0 -90 + 18b = 6 + 0 -90 + 18b = 6 Add '90' to each side of the equation. -90 + 90 + 18b = 6 + 90 Combine like terms: -90 + 90 = 0 0 + 18b = 6 + 90 18b = 6 + 90 Combine like terms: 6 + 90 = 96 18b = 96 Divide each side by '18'. b = 5.333333333 Simplifying b = 5.333333333
| 2x+180.4=56.8 | | -7(-7x+9)5= | | x/29.4=5.5/4.2 | | -55+5x=88-6x | | -20-4x=25-7x | | 3(x-7)-23=4(x-8)+22 | | -(x+2)+16=14 | | 27/9=18/x | | -(2x+6)-4=20 | | 7x-19=4x-2 | | 7.2/x=2.4/1.8 | | -125+2x=67-6x | | -(5x-10)+3(6x+5)= | | 17/12=x/36 | | 36x-1=3 | | 9x-3y=180 | | 3x-7=5x+21 | | 68/12=51/x | | 25=5/3(x-12) | | 2e+9=49 | | -3(x-8)+15=18 | | 8c+9=7c | | -2q=-q+7 | | 6x-y=6-y | | n/32=1/16 | | -76+x=-5x+74 | | -10+10t=9t | | 10x^2-6=954 | | 2-y/3=30 | | -4(-(x+5))=-16 | | (5x+14)+(x-5)= | | 3p+pq+-4pr= |